Effect of rice bran oil supplementation on milk composition, milk-free fatty acids and metabolic health status in dairy cows during mid-stage lactation - Paramintra Vinitchaikul; Korawan Srigerm; Jate Piapuk; Chaiwat Arjin (Veterinary Integrative Sciences)
The objective of this experiment was to evaluate the benefits of rice bran oil (RBO) supplementation in the dairy cow’s diet. Six crossbred Holstein-Friesian dairy cows were randomly assigned into a double 3 x 3 Latin square design. Three dietary treatments were applied as a basal diet (control), 2% and 4% RBO supplementation. The feeding trial was divided into three periods and each lasting four weeks. Feed samples were collected in each period. Milk composite samples were taken seven consecutive days during the fourth week. Free fatty acid milk samples were collected on the final day in each period. Blood samples for metabolic health and total antioxidant (TAS) status were collected at the end of third and fourth week in each period. The results revealed that supplementing with RBO had a significant (P<0.05) increased in milk protein and solid not fat. Moreover, there was a higher level (P<0.05) of oleic acid (C18:1-cis(n-9)) and may increase a proportion of linoleic acid (C18:2-cis(n-6)). Trend toward a decrease (P=0.10) in blood urea nitrogen (BUN) concentration was found. In addition, RBO supplementation was no significant (P>0.05) effect on metabolic profiles and TAS level. In summary, supplementation of RBO in dairy cow’s diet increased milk protein and solid not fat, while increase oleic acid (C18:1-cis(n-9)) level and might be a trend to decrease BUN levels. Supplemented with RBO up to 4% of dry matter intake have no negative effects on the metabolic health status of dairy cows. Although, RBO did not improve the antioxidant status.